AB0668 Effectiveness of individually tailored treatments in lupus nephritis: Data from 46 consecutive italian patients followed in a single center. (23rd January 2014) - Ramirez, G.A.; Bonavida, G.; Canti, V.; Rovere-Querini, P.; Manfredi, A.A.; Sabbadini, M.G.; Bozzolo, E.
Abstract : Background: Lupus nephritis is a major cause of morbidity and mortality among lupus patients [1]. Despite the large number of studies demonstrating the efficacy of immunosuppressive therapies [2-3], universal therapeutic guidelines haven't yet been developed to date. Moreover the clinical polymorphism of lupus nephritis dampens the application of rigid therapeutic protocols and stress the need for individually tailored treatments. Objectives: To assess the clinical outcome of a set of consecutive patients, receiving individually tailored treatments for their lupus nephritis. Methods: Clinical data (including hypertension, complement consumption, urinary sediment abnormalities, serum creatinine values and ongoing therapies) of 46 consecutive patients with lupus nephritis from a single reference center were recorded between 1992 and 2011 at baseline, at 6, 18 months and at the end of the follow up. Patients with class III/IV/V lupus nephritis were included. Results: Induction therapy with monthly cyclophosphamide (n=42) or mycophenolate (n=4) was performed during the first six months with a 30.4% rate of clinical remission. Patients who failed to achieve remission were maintaned with i.v. cyclophosphamide or shifted to mycophenolate and rituximab. Patients with persistent proteinuria received additional cyclosporin A [2]. Drug-related toxicity was reduced by bladder and gonad prophylaxis. Patients achieving sustained remission were shifted to azathioprine, mycophenolate or to therapy suspension. Nephritic reactivation was observed at least once in nine patients (19.6%). Mycophenolate or cyclophosphamide alone or in combination with cyclosporin and rituximab were used in patients who failed to achieve remission. Remission rates of 71.7% and 76.1% were obtained at 18 months and at follow up end respectively. Kidney survival was 100% at 18 months and 97.8% at the end of the follow-up. Complications occurred in 16/46 patients (34.8%). Conclusions: These data demonstrate that combinations of available therapeutic tools induce sustained clinical remission and low drug-related toxicity in patients with lupus nephritis. Further studies are necessary to elucidate the underlying factors conferring each individual her/his unique response profile to different treatments at different disease times. References: Isenberg, D. and P. Lesavre, Lupus, 2007. 16(3): p. 210-1. Ferrario, L., et al., Rheumatology (Oxford), 2000. 39(2): p. 218-220. Appel, G.B., et al., Mycophenolate mofetil versus cyclophosphamide for induction treatment of lupus nephritis. J Am Soc Nephrol, 2009. 20(5): p. 1103-12. Disclosure of Interest: None Declared